Iranian EFL Students’ Perceptions of Foreign Language Writing Anxiety and Perfectionism in Essay Writing - Ebrahim Khezerlou (Yayasan Visi Intan Permata, 2023)
Mastering writing skills is an essential criterion for EFL students who desire to fully invest in their academic discipline. While it is crucial to develop numerous writing abilities to communicate effectively, the research shows that the affective variables, such as self-esteem, perfectionism, stress, anxiety, and burnout, exert a profound negative influence both on the process and product of writing. To explore the devastating effects of these constructs beyond, the study aims to investigate the interactive impact of anxiety and perfectionism on essay writing among Iranian EFL students (n=85). The Second Language Writing Anxiety Inventory of Cheng (2004) and the Multidimensional Perfectionism Scale of Hewitt and Flett (1990) were employed to measure the participants’ perceived writing anxiety and perfectionism. A quantitative research method was employed in the collection and analysis of the data. The results showed a medium level of FL writing anxiety and perfectionism among the participants. They also revealed that the most prevalent types of anxiety and perfectionism among them were cognitive and self-oriented, respectively. Finally, the results disclosed a strong positive relationship between their anxiety and perfectionistic tendencies. Thus, it was concluded that anxiety and perfectionism may interactively challenge EFL students more in their writing activities. The results are beneficial in deepening the understanding of teachers and researchers in the field pedagogically and practically.